Antibacterial Effect of Luma apiculata (DC.) Burret Extracts in Clinically Important Bacteria - Tiare Araya-Contreras; Rhonda Veas; Carlos A. Escobar; Pamela Machuca; Mauricio Bittner (International Journal of Microbiology)
Nosocomial infections caused by bacteria are one of the main public health problems. Moreover, the resistance to antibiotics by these bacteria makes it necessary to find new treatments to fight them. Objective. To evaluate the antibacterial activity of Luma apiculata (DC.) Burret extracts on bacteria of clinical importance. Materials and Methods. In this study, extracts were obtained at room temperature by successive extraction of L. apiculata leaves, flowers, and branches and treated separately with solvents of ascending polarity (i.e., hexane, methylene dichloride, ethyl acetate, ethanol, methanol, and water) to extract the compounds depending on their polarity. Then, the extract’s antibacterial activity was tested against Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus saprophyticus, Enterococcus sp, Acinetobacter baumanii, Pseudomonas aeruginosa, and Escherichia coli. Results. The hexane extract of L. apiculata leaves resulted to be active against all bacteria tested. Among them, S. aureus showed to be the more susceptible, showing a minimum inhibitory concentration (MIC) of 120 μg/ml. In addition, a growth curve was performed, and colonies were counted. A decrease in bacterial growth was observed when the hexane extract of L. apiculata leaves was added. Besides, the hexane extracts of L. apiculata flowers resulted to be active against all Gram-positive tested bacteria. However, at higher concentrations, this extract resulted inactive for the Gram-negative bacteria tested. The hexane extract of L. apiculata branches resulted to be inactive in all cases. The extracts obtained treating separately leaves, flowers, or branches with solvents of major polarity than the hexane in a successive extraction of ascending polarity methodology resulted also to be inactive as an antimicrobial against all bacteria tested. Discussion/Conclusion. The hexane extract of L. apiculata leaves showed the lower MIC against S. aureus when compared with extracts obtained from other parts of the plant. The growth curve and the colonies count suggest a bacteriostatic activity of the L. apiculata leaves extract against Staphylococcus aureus.